CARDIOVASCULAR RISK AND CHRONIC KIDNEY DISEASE: CARDIO-NEPHROPROTECTION STRATEGIES - V. C. Moiseev; N. A. Mukhin; A. V. Smirnov; J. D. Kobalava; I. N. Bobkova; S. V. Villevalde; M. A. Yefremovtseva; L. V. Kozlovskaya; M. Yu. Shvetsov; M. V. Shestakova; G. P. Arutyunov; S. A. Boytsov; et al. (Российский кардиологический журнал, 2014)
.